2021
DOI: 10.1155/2021/8897111
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Investigation of Magnetic Field on Unsteady Boundary Layer Stagnation Point Flow of Water-Based Graphene Oxide-Water and Graphene Oxide-Ethylene Glycol Nanofluid over a Stretching Surface

Abstract: This study explains the effect of magnetic field of the stagnation point flow of a water-based nanofluid graphene oxide-water (GO-W) and graphene oxide-ethylene glycol (GO-EG). Heat transfer analyses are discussed by converting the given partial differential equation into a nonlinear ordinary differential equation using the similarity transformation and solved using an approximate analytical method, namely, the optimal homotopy analysis method (OHAM), to obtain an approximate analytical solution of the nonline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 31 publications
1
2
0
Order By: Relevance
“…Tables 2 and 3 were calculated to compare the present outcomes of the skin friction C f Re s ð Þ 1=2 with published values in Mabood and Das (2016), Imtiaz et al (2016) and Imtiaz et al (2019) for several values of the curvature parameterK, the fluid parameter a 1 and the magnetic parameter M . Additionally, these two tables have shown that, the skin friction decreases as both of the magnetic which is the same results observed by Rehman and Salleh (2021) and the fluid parameters increase, whereas it increase as the curvature parameter increases. Here, the calculated percentage relative error« refers to a suitable and an excellent agreement.…”
Section: Resultssupporting
confidence: 83%
“…Tables 2 and 3 were calculated to compare the present outcomes of the skin friction C f Re s ð Þ 1=2 with published values in Mabood and Das (2016), Imtiaz et al (2016) and Imtiaz et al (2019) for several values of the curvature parameterK, the fluid parameter a 1 and the magnetic parameter M . Additionally, these two tables have shown that, the skin friction decreases as both of the magnetic which is the same results observed by Rehman and Salleh (2021) and the fluid parameters increase, whereas it increase as the curvature parameter increases. Here, the calculated percentage relative error« refers to a suitable and an excellent agreement.…”
Section: Resultssupporting
confidence: 83%
“…For more detailed information, see refs. [10][11][12][13][14][15][16][17][18]. Shafiq et al [19] investigated activation energy and binary chemical reactions with the influence of an artificial intelligence approach in 3rd grade nanofluid.…”
Section: Introductionmentioning
confidence: 99%
“…Two dimensional MHD Prandtl fluid flow over stretching sheet was studied by (25) . The effect of magnetic field of the stagnation point flow of water base nano fluid was discussed by (26) . The MHD Prandtl nano fluid over a stretched sheet was investigated by (27) with convective boundary condition.…”
Section: Introductionmentioning
confidence: 99%